Manajemen Sekolah Berbantuan Tehnologi Informasi Di Mentari Kids Kec. Tulung Kab. Klaten - Riyadi, Moh, Dr Eko Supriyanto, Dr Suwadji (2017)
Purpose of this study was to measure the implementation of curriculum management, finance and infrastructure, public relations and special services aided management of information technology in the KB Mentari Kids Tulung Klaten Forms of this study is qualitative case study approach, withdrawal data using an interactive model that includes data reduction, data presentation, and data verification. Result of research in the field, namely their use of information technology applications, administrative assistant students who use the application Asisten Versi 2.0.2 Gratis, SIPPAUD versi 2.1.6, www.mentariku.org, www.mentarikids.com, and Applikasi Pendataan PAUD DIKMAS. The application is very helpful in the areas of curriculum, student section, financial personnel, preventif infrastructure, public relations and menegement special services. Some modern devices such as the the internet, computer, laptops, printers, LCD projector, tape recorders, television, camcorder part of the utilization of technology